Onyms in Political Posters: Intersemiotic and Pragmatic Perspectives - Svetlana Yu. Pavlina (Вопросы ономастики, 2023)
This article explores the properties of proper names involved in visual political communication from the standpoint of multimodality and functional pragmatics. The material encompasses 198 campaign posters, spanning 1999–2022, which have a verbal element containing anthroponyms, toponyms and other proper names. Such political advertisements incorporate linguistic and visual elements so they are viewed as multimodal texts in which politically relevant information is created due to the integration of various modes. The research rests in the realm of socio-onomastics and uses the systemic functional approach to multimodal discourse analysis. The ﬁndings show that in juxtaposition to other semiotic signs, an onym’s meaning is equally conditioned to the internal semantics and broad social and cultural contexts. Hence, functionally, they are a part and parcel of those complex semiotic relations shaping the message and the image-language models of the visual political discourse. The research elucidates the functions names perform in political posters which encompass identiﬁcation, attention drawing, ludic, identity assessment and evaluation ones. The ﬁndings have implication for studying the manipulative potential of proper names set in a socio-political context.